Startups and Entrepreneurship Programme: Self-Employment and Economic Empowerment in India - Gurwinder Kaur (Department of Public Administration, Parahyangan Catholic University, 2025)
The objective of this paper is to analyse startups and entrepreneurship programmes in India. There is an essential requirement to strengthen abilities in areas marked by actual skill gaps since self-employment provides a potential pathway to addressing unemployment. Entrepreneurship has a significant role in economic progress, and its creation of jobs is a common accolade for its practitioners. Self-employment offers a chance to overcome unemployment and poverty. The recent economic recession has led to a substantial surge in self-employment and business start-ups in many modernised economies, as people displaced sought to leverage their skills or pursue new opportunities. The small, independently owned businesses have a positive impact on the social, environmental, and economic development of the state and country. The Government of India launched a variety of initiatives to support businesses and startups. This article suggests a framework that outlines the use of innovation by policymakers in decision-making to promote innovation, startup entrepreneurship, and economic growth.